POTENSI LAPANGAN PANAS BUMI GEDONGSONGO SEBAGAI SUMBER ENERGI ALTERNATIF DAN PENUNJANG PEREKONOMIAN DAERAH - Setyaningsih, Wahyu (Jurnal Geografi, 2014)
Indonesia as a country with over than 300 million people population needsalternative sources of energy to overcome the future energy crisis. Based ontectonic conditions, Indonesia is a country rich in geothermal sources which canbe utilized as an alternative energy source, especially for power generation andas supporting tools to industry, agriculture, fisheries and other potential areasdevelopment. Semarang district has sufficient geothermal potential to bedeveloped, such as Gedongsongo geothermal field. Temperatures were obtainedusing the method of gas Geothermometer Fumarole in Gedongsongo is at 223ÂºC,thus Gedongsongo geothermal areas have highly potential for electric power andother economic activities. In the future, this potential can be utilized as analternative energy source that could be capable to fullfilled the community needs.